2006
DOI: 10.1302/0301-620x.88b2.16830
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the tendon of latissimus dorsi for the treatment of massive tears of the rotator cuff

Abstract: We describe 14 patients who underwent transfer of latissimus dorsi using a new technique through a single-incision. Their mean age was 61 years (47 to 76) and the mean follow-up was 32 months (19 to 42).The mean Constant score improved from 46.5 to 74.6 points. The mean active flexion increased from 119˚ to 170˚, mean abduction from 118˚ to 169˚ and mean external rotation from 19˚ to 33˚. The Hornblower sign remained positive in three patients (23%) as did the external rotation lag sign also in three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
102
0
27

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 21 publications
7
102
0
27
Order By: Relevance
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 65%
“…None of our patients could control the spatial positioning of their arm, as demonstrated by positive preoperative dropping, lag, and hornblower signs. Review of the literature suggests the reported gain in active external rotation after an isolated transfer of the LD is modest, but patient satisfaction remains high because the arm is stabilized by the transfer [1,2,18,23,30,35,47]. Gerber [19] has recently reported a similar series of patients treated with a LD transfer and reverse shoulder arthroplasty; his preliminary results suggested similar promise but demonstrated a lower gain in external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, progression of osteoarthritis and decrease of acromiohumeral distance were reported for the latissimus dorsi transfer [10,12,16].…”
Section: Discussionmentioning
confidence: 96%
“…For treatment of posterosuperior rotator cuff tears, Gerber et al [8,11] and others [1,12,16,23] have described transfer of the latissimus dorsi tendon sutured to the insertion site of the supraspinatus tendon using a twoincision technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation